Analysis of the Level of Financial Technology in Students of the Faculty of Economics UNCEN in 2025 - Rumbiak, Yensawai E.; Aswad, Muhammad (West Science Interdisciplinary Studies, 2025)
The purpose of this study is to determine the basic level of understanding of financial technology literacy among students of the Faculty of Economics and Business, Cenderawasih University. The respondents in this study amounted to 100 people and all of them are active students of the Faculty of Economics and Business, Cenderawasih University. Data collection used online questionnaires and library studies. The questionnaire was designed to measure students' financial technology literacy. The data obtained were processed with descriptive statistical analysis. The results of the analysis show that in general, students of the Faculty of Economics and Business have knowledge of financial technology literacy that is in the high average category. It is hoped that the results of this study can be a source of reference for the Faculty and Cenderawasih University as well as policy makers in this case the authorities and related communication and informatics services to support programs to increase understanding of financial technology literacy for students as the next generation of the development of the nation and state. Especially students of the Faculty of Economics and Business in contributing their knowledge to the business world. It is hoped that the Faculty of Economics, Cenderawasih University and the Government can support the development of student understanding and knowledge so that it has an impact on increasing competitive MSMEs.